2005
DOI: 10.1183/09031936.05.00107404
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle inflammation and nitric oxide in patients with COPD

Abstract: In chronic obstructive pulmonary disease (COPD) the presence of systemic inflammation has been associated with peripheral muscle abnormalities and weight loss.To study whether inflammatory factors are important in these processes, the present study compared the skeletal muscle levels of nitrite, nitrate, nitrotyrosine, neuronal, endothelial and inducible nitric oxide synthases (nNOS, eNOS, and iNOS, respectively), and inflammatory markers (tumour necrosis factor (TNF)-a, CD154 and CD163) in 15 patients (forced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
71
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 35 publications
9
71
2
1
Order By: Relevance
“…However, it is also possible that the decline results from the development of more advanced systemic involvement of COPD [28]. This hypothesis is further supported by the observations of AGUSTI et al [29], who showed worsening apoptosis in muscle biopsies of patients with COPD, and by MONTES DE OCA et al [30] who described increased levels of markers of oxidative stress and infiltration by macrophages in patients with severe COPD compared with controls. In addition, worsening Charlson comorbidity scores over time in the present study suggest a possible role for increasing comorbidity as the population aged.…”
Section: Discussionsupporting
confidence: 74%
“…However, it is also possible that the decline results from the development of more advanced systemic involvement of COPD [28]. This hypothesis is further supported by the observations of AGUSTI et al [29], who showed worsening apoptosis in muscle biopsies of patients with COPD, and by MONTES DE OCA et al [30] who described increased levels of markers of oxidative stress and infiltration by macrophages in patients with severe COPD compared with controls. In addition, worsening Charlson comorbidity scores over time in the present study suggest a possible role for increasing comorbidity as the population aged.…”
Section: Discussionsupporting
confidence: 74%
“…In resting quadriceps muscles of patients with severe COPD, total glutathione concentrations are lower whereas the levels of HNE and lipofuscin (products of lipid peroxidation) are signifi cantly higher than those detected in control subjects (Engelen et al 2000a;Allaire et al 2002;Barreiro et al 2003). In addition, resting limb muscles of COPD patients have increased protein tyrosine nitration and elevated levels of iNOS protein, suggesting the development of nitrosative stress (Barreiro et al 2003;Montes de Oca et al 2005). With respect to exercise, patients with moderate to severe COPD have elevated ROS-induced DNA damage in peripheral blood mononuclear cells, plasma uric acid, blood oxidized glutathione and lipid peroxides levels at the end of whole body exercise indicating that these patients experience systemic oxidative stress, even during normal daily activity (Vina et al 1996;Heunks et al 1999;Mercken et al 2005).…”
Section: Oxidative and Nitrosative Stressmentioning
confidence: 97%
“…Few studies have as yet explored whether or not NO production and NOS expression are altered in skeletal muscles of COPD patients. Several studies have reported that the levels of nNOS and eNOS proteins in quadriceps of patients with severe and moderate COPD are similar or even lower than that those of control subjects (Barreiro et al 2003(Barreiro et al , 2008aMontes de Oca et al 2005). In comparison, others described induction of the iNOS isoform in quadriceps of patients with severe COPD patients, particularly those with low BMI ( .…”
Section: Nitric Oxide Synthasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired insulin sensitivity in skeletal muscle is a major feature of type 2 diabetes [12]. An increased amount of TNF-α protein in skeletal muscle has been found in patients with insulin resistance [13] and chronic obstructive pulmonary disease [14]. Regular exercise improves insulin sensitivity [15] and the amount of TNF-α protein is reduced by resistance exercise in frail elderly patients [16].…”
mentioning
confidence: 99%